2018
DOI: 10.1002/14651858.cd007419.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vascular endothelial growth factor for diabetic macular oedema: a network meta-analysis

Abstract: Anti-vascular endothelial growth factor for diabetic macular oedema: a network meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 103 publications
5
126
0
5
Order By: Relevance
“…2 Current treatments involve anti-VEGF therapies alone or combined with another medication or laser photocoagulation. 3,4 Autonomic innervation of the eye includes sympathetic and parasympathetic pathways via different nerves, including those originating from the superior cervical ganglion (SCG) and pterygopalatine ganglion. 5 Several lines of evidence suggest a critical role of the sympathetic nervous system in maintaining ocular vascular homeostasis.…”
Section: Purposementioning
confidence: 99%
“…2 Current treatments involve anti-VEGF therapies alone or combined with another medication or laser photocoagulation. 3,4 Autonomic innervation of the eye includes sympathetic and parasympathetic pathways via different nerves, including those originating from the superior cervical ganglion (SCG) and pterygopalatine ganglion. 5 Several lines of evidence suggest a critical role of the sympathetic nervous system in maintaining ocular vascular homeostasis.…”
Section: Purposementioning
confidence: 99%
“…[5][6][7] Multiple large-scale randomized clinical trials concerning the safety of intravitreal anti-VEGF injections revealed no significant increase in systemic risk focused on serious adverse events (cerebrovascular accident, ischemic heart disease, systemic thromboembolism, etc.). [8][9][10][11] However, there are few studies on proteinuria after intravitreal bevacizumab (IVB) injection in patients with diabetes. 12,13 Recently, there was a case series reporting worsened proteinuria after multiple IVB injections in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…VA at baseline has previously been described as an independent predictor of visual and structural outcomes following treatment with anti-angiogenic therapy in DME. 24 The median BCVA was 60 letters in this cohort. This cut off was used to stratify our results accordingly.…”
Section: Outcomes Stratified By Baseline Visual Acuitymentioning
confidence: 68%